THE ANALYSIS OF MODERATING MARKETING STRATEGY AS OF AI, BRAND IMAGE & PRODUCT QUALITY ON IPHONE PURCHASING DECISIONS - Muhammad Ilham Oetomo (PT. Media Akademik Publisher, 2026)
Amidst the deindustrialization phenomenon in Indonesia and Inspired by the success story of Apple Inc., which is now also facing challenges in the VUCA era, this study examines the influence of artificial intelligence (AI) technology, brand image, and product quality, along with their interaction as marketing strategies that moderate consumer purchase decisions for the iPhone. Using a mixed methods approach, quantitative data were analyzed from a sample of 97 iPhone user respondents and also other statistical data from platforms that revealed a significant positive relationship in all tested hypotheses. This research is also supported qualitatively by the analysis of the latest insights from other data such as field facts, literature studies and previous research. Since there is no previous research that simultaneously highlights the important role of comprehensive AI features, premium brand perception, and superior quality implemented with effective marketing strategies in increasing the attractiveness of iPhone purchasing decisions, this research provides a new theoretical contribution to the development of modern marketing management studies and rather has practical implications for management practitioners & entrepreneurs in designing progressive marketing strategies for the industry.